2006
DOI: 10.1026/0033-3042.57.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Ein psychologisches Rahmenkonzept zur Analyse von Fusions- und Akquisitionsprozessen

Abstract: Zusammenfassung. Der Artikel gibt einen Überblick zur aktuellen Forschung über Fusionen und Akquisitionen (M&A) aus psychologischer Perspektive. Basierend auf dem Rahmenkonzept der Psychologie von M&A von Hogan und Overmyer-Day (1994) werden Variablen aufgeführt, die zentral sind für die Analyse von Fusions- und Akquisitionsprozessen, da sie den Erfolg eines Unternehmenszusammenschlusses beeinflussen. Zum einen ergänzen wir dieses Modell durch Faktoren, die sich aus psychologischen Theorien ableiten un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Emotional reactions to perceived fit thus complete the picture of the underlying process. These results are in line with the conceptual model of psychological reactions to mergers provided by Hogan and Overmyer-Day (1994) as well as Klendauer et al (2006), who stated that the psychological success of a merger depends on multiple causes such as justice perception as well as emotional reactions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Emotional reactions to perceived fit thus complete the picture of the underlying process. These results are in line with the conceptual model of psychological reactions to mergers provided by Hogan and Overmyer-Day (1994) as well as Klendauer et al (2006), who stated that the psychological success of a merger depends on multiple causes such as justice perception as well as emotional reactions.…”
Section: Discussionsupporting
confidence: 90%
“…Giessner and colleagues (2006) found that support from members of the organization for the merger (e.g., employees) for a specific merger patterns varied as a function of premerger status. Here, merger support is conceptualized as a subjective evaluation of organizational members (e.g., employees) in terms of their attitudes towards the merger (Klendauer, Frey, & Greitemeyer, 2006;Mottola et al, 1997) and depends on a favourable social comparison with the merger partner (see also Gleibs et al, 2010). Thus, organizational members in a merger process could positively evaluate the merger if they think that their premerger organization is well-represented in terms of previous strength and least threatening in terms of job status, security, and identity.…”
Section: Merger Patterns and Merger Supportmentioning
confidence: 99%
“…Problems regarding mergers' success or failure are often ascribed to resistance to change by organizational members involved in the merger (e.g., Haunschild, Moreland, & Murrell, 1994). For example, previous research has shown that mergers create behavioral and psychological reactions in organizational members such as stress, turnover intentions, lower self-esteem, anxiety, and illness leading to reduced job satisfaction and increased resistance (e.g., Cartwright, 2005; Hogan & Overmyer-Day, 1994; Klendauer, Frey, & Greitemeyer, 2006; Terry, Callan, & Sartori, 1996).…”
mentioning
confidence: 99%